Naturally occurring variants in the transmembrane and cytoplasmic domains of the human Coxsackie- and adenovirus receptor have no impact on virus internalisation - Herrmann, Leonie; Filip, Adrian; Lapuente, Dennis; Tenbusch, Matthias; Niehaus, Karsten; Rudolph, Volker; Farr, Martin (Biochemical and Biophysical Research Communications, 2020)
The Coxsackie- and adenovirus receptor (CAR) mediates homophilic cell-cell contacts and susceptibility to both human pathogenic viruses through its membrane-distal immunoglobulin domain. In the present study, we screened five missense variants of the human CAR gene for their influence on adenovector or Coxsackievirus entry into Chinese hamster ovary cells. The CAR variants facilitated virus internalisation to a similar extent as wild type CAR. This underlines CAR's presumed invariance and essential physiological role in embryogenesis.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Coxsackievirus and adenovirus receptor; Genetic variants; Viral infection